Ready-to-eat cereal and milk for breakfast compared with no breakfast has a positive acute effect on cognitive function and subjective state in 11–13-year-olds: A school-based, randomised, controlled, parallel groups trial - Adolphus, Katie; Hoyland, Alexa; Walton, Jenny; Quadt, Frits; Lawton, Clare L.; Dye, Louise (Springer, 2021)
Purpose: We tested the acute effect of breakfast (ready-to-eat-cereal [RTEC] and milk) versus (vs.) no breakfast on cognitive function and subjective state in adolescents. Methods: Healthy adolescents (n = 234) aged 11–13 years were recruited to take part in this school-based, acute, randomised, controlled, parallel groups trial with two interventions; Breakfast or No Breakfast. The breakfast intervention consisted of ad libitum intake of RTEC (up to 70 g) with milk (up to 300 ml) administered in a naturalistic school breakfast programme environment. Cognitive function was assessed at baseline and + 70 and + 215 min post-intervention in a group-testing situation, similar to a school classroom context. The CANTAB test battery included: Simple Reaction Time (SRT), 5-Choice Reaction Time (5-CRT), Rapid Visual Information Processing (RVIP), and Paired Associates Learning (PAL; primary outcome). Data collection commenced January 2011 and ended May 2011. This trial was retrospectively registered at www.clinicaltrials.gov as NCT03979027 on 07/06/2019. Results: A significant effect of the intervention (CMH[1] = 7.29, p < 0.01) was found for the number of levels achieved on the PAL task. A significant difference between interventions was found when baseline performance reached level 2 (JT, z = 2.58, p < 0.01), such that 100% of participants in the breakfast intervention reached the maximum level 4 but only 41.7% of those in the no breakfast intervention reached level 4. A significant baseline*intervention interaction (F[1,202] = 6.95, p < 0.01) was found for total errors made on the PAL task, indicating that participants who made above-average errors at baseline reduced the total number of errors made at subsequent test sessions following breakfast consumption whilst those in the no breakfast intervention did not. There was a positive effect of breakfast on reaction time and visual-sustained attention. The results also demonstrated interactions of intervention with baseline cognitive performance, such that breakfast conferred a greater advantage for performance when baseline performance was poorer. Conclusion: Consuming breakfast has a positive acute effect on cognition in adolescents.